2015
DOI: 10.5721/eujrs20154844
|View full text |Cite
|
Sign up to set email alerts
|

Discriminant analysis of olive oil mill wastes using spectroradiometers in the visible and near infrared part of the spectrum

Abstract: This paper aims to introduce an index which is able to assist the recognition of Olive Oil Mill Wastes (OOMW) disposal areas using multispectral satellite images. For this purpose several ground spectroradiometric measurements in the range of 450 -900 nm have been collected at a variety of targets. The samples were initially resampled to the GeoEye-1 sensor using the appropriate Relative Spectral Response Filter (RSR) and then scatter plots and spectral signatures were projected. Then an evaluation of nine wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
(20 reference statements)
1
9
0
Order By: Relevance
“…The application of different image analysis algorithms indicated that PCA analysis can be effectively used for mapping OMW ponds. Furthermore, the SVM classification algorithm showed optimum performance in differentiating and identifying OMW sites from neighbor areas, as it was proved by Agapiou et al [16]. It is noteworthy to mention that, within our research, Composite 3 was used with images acquired during the winter period (February 2020).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The application of different image analysis algorithms indicated that PCA analysis can be effectively used for mapping OMW ponds. Furthermore, the SVM classification algorithm showed optimum performance in differentiating and identifying OMW sites from neighbor areas, as it was proved by Agapiou et al [16]. It is noteworthy to mention that, within our research, Composite 3 was used with images acquired during the winter period (February 2020).…”
Section: Discussionsupporting
confidence: 61%
“…In this concept, several studies have employed satellite images for monitoring environmental parameters, especially water bodies, that are affected mainly by severe anthropogenic activities [14,15]. In the recent past, satellite remote sensing integrated with a compilation of in situ spectral signature libraries have been also utilized to identify and monitor OMW disposal sites [4,16].…”
Section: Introductionmentioning
confidence: 99%
“…Ground spectroradiometers and geophysical surveys can be also used for monitoring OOMW areas. Such ground technologies may be used so as to further optimize the system and the GIS procedures [15,31] and to examine underground pollution. The system will be able to record in a 4D space (X,Y,Z and time) the OOMW areas for the island of Crete.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, only a limited number of publications exist related to this topic [14][15][16]. This relative low number of publications should be linked to the local problem of OOMW disposal areas in the Mediterranean countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation